Plano de desenvolvimento institucional: proposta de um modelo de referência e de automatização para IFES - Mendonça, Lucas Cezar (2017)
The present work aims to evaluate the management of the Institutional Development Plan (IDP) in the Brazilian Federal Universities and starting from the diagnosis, to propose artifacts and guidelines of support for the IPD elaboration and management in these organizations. A theoretical approach which contemplates the Brazilian public administration model, methodologies of strategic planning in public organizations, concepts of strategic planning and IPD, together with budgetary concepts (which play an important role in the public planning) have been used. As a result of the diagnosis a lack of support to the public administrators in the Federal Higher Education Institutions (FHEI) was observed, which in turn made the proposition of a reference document and of a software instrument possible as a support to the administrators in the IPD elaboration and management. These artifacts and guidelines proposed are included in a bigger proposal that represents the FORPDI project, which was originated in the Forum of the Planning and Administration Pro-Rectors -FORPLAD - of the FHEIs and that has the conceptual and financial support of the Ministry of Education in the search for the improvement of the strategic planning of the Universities.